Cyber Threats and Prevention Methods in the Digital Economy - Anafiyaev Abdurashid Mamasidikovich; Shokirova Sarvinoz Oybekovna (Genius Journals, 2022)
As the country's infrastructure quickly develops with a digital overlay over the next few decades, billions of sensors will be attached to highways, buildings, power plants, companies, and even residences. Increased digitalisation helps the government and commercial enterprises use data to manage this crucial infrastructure, but it also leaves them vulnerable to cybersecurity threats. This paper investigates cyber dangers in the digital economy and preventative methods
Keywords: Digitalization; cybersecurity; ICT; digital economy